Scholar, Serpent, Yogin, and Devotee: The Many Faces of Patañjali in Indian Traditions - Bühnemann, Gudrun, (Asian Studies E-Books Online, Collection 2026., 2026)
This study illuminates the many faces of Patañjali in Indian traditions. Often regarded as an incarnation of the cosmic serpent Ādiśeṣa or Anantanāga, Patañjali is celebrated, in both story and art, as a grammarian, scholar and practitioner of yoga, physician-alchemist, medical authority, teacher, ascetic, and devotee of the Dancing Śiva (Naṭarāja). The first three chapters examine the literary works attributed to Patañjali, explore legendary accounts and beliefs associated with this multifaceted figure, and survey temples and shrines dedicated to the sage. The following five chapters trace the development of Patañjali's iconography from its earliest forms in Tamilnadu, South India, to contemporary examples.